ORGANISASI PEMBELAJARAN, KOMPETENSI DAN KINERJA KARYAWAN BANK XXX DI JAKARTA - Rahardjo, Thea Herawati; Purwanto, Purwanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, Universitas Tarumanagara, 2017)
This study aimed to determine empirically learning organization have affect to competence, competence have significant affects to performance, learning organization through competence have significant affect to performance. The method used in sampling was simple random sampling, a total of 200 employee at Bank “XXX” in Jakarta The data analysis technique used is Structural Equation Modeling (SEM), using by LISREL versi 8.8 are need to test the hypothesis. The results showed, learning organization give effect competence, competence give effect performance, learning organization through competence give effect performance which means that the research hypothesis tested.Through these results can be material for the attention of Bank “XXX”to keep improving the learning organization, competence heve affect the performance of the business, because through good performance can affect the competitive advantage for Bank XXX” in running the business.Keywords: Learning organization, Competence, Performance, SEM